Pentapartitioned neutrosophic set and its properties - Rama Mallick; Surapati Pramanik (Neutrosophic Sets and Systems, 2020)
The main objective of this paper is to propose a new type of set which we call pentapartitioned neutrosophic set. We also prove some of its basic properties.